Formation of the Conscience: Pedagogic Acting or Bargaining? - Vam Der Tiun, Leo (Horyzonty Wychowania, 2017)
After a short historical draft of the pillarized Dutch society andthe praxis of the formation of conscience in the time of „RichRoman Catholic Life”, a picture is made of the once tolerant andin the meantime extremely secularized Netherlands, which isoften called a leading country in political and ethical issues andan experimental garden of religiosity.Next the focus is on evil in our time. The conception of sin andawareness of guilt have changed in the previous decades underthe influence of secularization and individualization.The question is now aggravated to the experience of evil andthe formation of conscience in the subculture of youth. A glanceis taken at their world of the Internet and TV, of chatting on theNet and video clips on the music channels MTV and TMF. Thereis the question of the relation between violence and sex in themedia and youth’s behaviour. Finally, this leads to the question as to what the formation of conscience means nowadays. The formation of conscience is animportant aspect of upbringing. And this can be done in variousways: in the way of passing on cultural achievements, in the way of allowing what is present in the educandus to develop, in theway of the communicative exchange of ideas and in the way ofactive presence close to the educandus, which seems to be themost proper way in this modern world and time.